Nietzsche’s Sting: What We Can Learn from the Peculiar History of Nietzsche’s Influence - Adolphi, Rainer (Sententiae, 2024)
The essay shows what Nietzsche means as a phenomenon of time (Erfahrungsgehalt) – and how an awareness of his possible significance for the present (including possible dangers) can be gained from the history of his impact. Which endeavor to understand the age and critique of social mentalities has turned to Nietzsche’s philosophy – and in which specific constellations – varies greatly. At the beginning of the 20th century, and repeatedly in crises since then, there was an attraction to total identification; today, on the other hand, Nietzsche is usually received as a fruitful type of thought that can be relatively independent of agreementwith all his theses and judgments. In this, Nietzsche stands as a model for a self-criticism of modernity (and for a transformation, but not an abandonment of rationality). – The several factual dimensions of this critique are shown; and how culture, morals and the sciences as well as social realities in particular have already become so ›Nietzschean‹ today that precisely the success story of Nietzsche’s thinking could conceal many things if it is limited to pure cultural or mental critique and does not also integrate other theorems: Nietzsche must not remain a solitaire..